A composite tailings porous ceramic ball and preparation method thereof

Through scientific proportioning and forming processes, porous ceramic balls are prepared using tailings and waste materials, which solves the problems of composition stability, sintering temperature and adhesion, pore uniformity and strength and hardness of tailings ceramic balls, and achieves low-temperature sintering and pore uniformity, which meets the requirements of environmental protection and sustainable development.

CN116655351BActive Publication Date: 2025-03-18JIANGSU JINSHI GRINDING CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310165763.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2025-03-18
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively use tailings to prepare porous ceramic balls, which have challenges in composition stability, sintering temperature and adhesion problems, pore size and distribution uniformity, and strength and hardness.

Method used

Through scientific and reasonable ratios, the molding process of main balls and cladding layers and the micro-positive pressure oxidation atmosphere sintering scheme are used to prepare uniform pore tailings ceramic balls, and the sintering temperature is controlled at 1100-1300℃, and materials such as zeolite tailings and coal gangue are used to control pore uniformity and strength.

Benefits of technology

It has achieved low temperature sintering of ceramic balls, improved pore uniformity and strength, consumed waste minerals to the greatest extent, and met the requirements of environmental protection and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116655351B_ABST
    Figure CN116655351B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite tailings porous ceramic ball, comprising a main sphere and a coating layer, wherein the main sphere comprises the following main materials in weight percentage: 30-60% iron tailings, 10-40% coal gangue, 20-50% bauxite tailings, 1-10% zeolite tailings, and 5-10% blast furnace slag; the coating layer comprises a coating material, wherein the coating material is one or more of alumina, kaolin, and bauxite. The present invention also discloses a preparation method of a composite tailings porous ceramic ball. The innovation of the present invention is that all tailings and waste materials are used, and uniform-pore tailings ceramic balls are prepared through scientific and reasonable proportioning, which consumes waste minerals to the greatest extent, and the ceramic sintering temperature is low, which is in line with environmental protection and sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of porous ceramic balls, in particular to a composite tailings porous ceramic ball and a preparation method thereof. Background Art

[0002] There are various types of tailings. According to the mineral processing process, there are gravity separation tailings, magnetic separation tailings, hand separation tailings, chemical separation tailings, flotation tailings, electrostatic separation and photoelectric separation tailings; and from the type of ore, common tailings include copper tailings, lead-zinc tailings, molybdenum tailings, gold-silver tailings, iron tailings, coal tailings, uranium tailings, bauxite tailings, etc. The tailings produced in different regions, different mineral processing processes and different ore types have very different compositions. The development and utilization of tailings cannot be generalized. It is necessary to conduct in-depth analysis on a mining area, a mineral processing process or a type of tailings to effectively utilize the tailings.

[0003] Tailings storage occupies a large amount of land, and improper handling can also cause mudslides, soil erosion, heavy metal pollution, dust pollution, etc. The pollution of water, soil, and air by various types of tailings seriously affects the ecological balance of various regions. Therefore, it is urgent to strengthen the management and comprehensive utilization of tailings.

[0004] Tailings utilization is beneficial to the country and the people, but we must also prevent improper use of tailings and secondary pollution. Tailings contain suspended matter, acid and alkali, heavy metals, arsenic, fluorine, mineral processing agents, chemical oxygen-consuming substances and other pollutants such as oil, phenol, ammonium, phosphine, etc., which are also important factors that hinder the transformation of tailings from waste to treasure, and require the joint efforts of scientific research and technical personnel and factories and enterprises.

[0005] Using tailings to produce porous ceramics and expanded foam ceramics is also a good way to consume and utilize tailings. To use tailings to prepare porous ceramic balls, the first thing to do is to solve the problem of tailings component stability, followed by the sintering temperature and sintering adhesion of tailings porous ceramics, as well as the pore size and distribution uniformity of tailings porous ceramics, and the strength and hardness of tailings porous ceramics. So far, there are few reports on the preparation method of porous tailings ceramics that can solve the above problems at one time.

[0006] The preparation processes of porous ceramics include: adding pore-forming agent process, particle stacking process, organic foam impregnation process and foaming process, etc. Different preparation processes have different characteristics and applicable scopes, and correspondingly there are certain problems and defects.

[0007] Patent No. CN202210960091.8 discloses a low-shrinkage mullite-based porous ceramic and a preparation method thereof. The foaming slurry is prepared by mixing ceramic slurry, gelling agent, foaming agent, etc., and then gelled in a mold, dried, and sintered to obtain a low-shrinkage mullite-based porous ceramic. The preparation process of this method is simple and suitable for mass production, but 5-10% gelling agent and 1-5% foaming agent are added, and the volatile matter is burned, which causes great environmental pollution, and the pore size cannot be controlled.

[0008] The patent number is CN202210546137.1, which discloses a method for preparing low-temperature porous ceramic materials. First, a low-temperature ceramic slurry is prepared, and then a porous polyurethane template is immersed in the low-temperature ceramic slurry. After hanging the slurry, it is dried to obtain a porous ceramic precursor; finally, the porous ceramic precursor is sintered in steps at 300-400°C and 650-700°C in N2 atmosphere. It has the advantages of low sintering temperature and uniform and controllable pores, but the preparation process is relatively complicated and difficult to control.

[0009] The patent number is CN201810294115.4, which discloses a new type of sound-absorbing material for construction and a preparation method thereof, which is made of the following raw materials in weight percentage: 36-40% steel slag powder, 25-29% clay, 17.5-20% polymethyl methacrylate, 3-4% albite, 4-5% starch, 1.7-2% stabilizer, 2-4% glass fiber, 2-3% reinforcing agent and 0.3-0.6% gelling agent; the sound-absorbing material for construction is prepared by combining particle stacking with the addition of a pore-forming agent, and the porosity can reach more than 60%, the material compressive strength is 10.0-12.0MPa, the simply supported beam notched impact strength is 19-23KJ / m2, and the sound absorption coefficient is above 0.64. It has good sound absorption effect and excellent mechanical properties, but it is difficult to control the particle stacking voids and the pore uniformity and pore size of the pore-forming agent. Summary of the invention

[0010] The purpose of the invention is to provide a composite tailings porous ceramic ball.

[0011] The invention also provides a method for preparing the composite tailings porous ceramic balls.

[0012] The innovation of the present invention is that all tailings and waste materials are used, and uniform-pore tailings ceramic balls are prepared through scientific and reasonable proportions, which consumes waste minerals to the greatest extent and has a low ceramic sintering temperature (the sintering temperature is 1100-1300°C); at the same time, a unique main ball and coating layer molding process is used to facilitate the static sintering of porous ceramic balls without mutual adhesion; a slightly positive pressure oxidizing atmosphere sintering scheme is also used, which is conducive to pore homogenization.

[0013] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is:

[0014] A composite tailings porous ceramic ball, comprising a main ball and a coating layer, characterized in that the main ball comprises the following main materials in weight percentage: 30-60% iron tailings, 20% coal gangue

[0015] 10-40%, bauxite tailings 20-50%, zeolite tailings 1-10%, blast furnace slag 5-10%; the coating layer includes a coating material, and the coating material is one or more of alumina, kaolin, and bauxite.

[0016] Furthermore, the iron tailings include the following components in mass percentage: Al2O3 5-18%, SiO2 45-70%, CaO 2-15%, MgO 2-10%, and Fe2O3 8-15%.

[0017] Furthermore, the coal gangue comprises the following components in mass percentage: Al2O3 25-40%, SiO2 40-50%, CaO 0.5-2%, Na2O 0.2-3.0%, K2O 0.1-1.5%, Fe2O3 0.5-5%, and C 5-15%.

[0018] Furthermore, the bauxite tailings include the following components in mass percentage: Al2O3 40-60%, SiO2 20-40%, CaO 0.3-1.5%, Na2O 0.05-2.0%, K2O 0.5-3.0%, Fe2O3 5-12%, and TiO2 1-5%.

[0019] Furthermore, the zeolite tailings include the following components in mass percentage: Al2O3 15-30%, SiO2 60-75%, CaO 2.0-4.0%, Na2O 1.0-3.0%, K2O 2.0-4.0%, and Fe2O3 0.5-3%.

[0020] Furthermore, the blast furnace slag includes the following components in mass percentage: Al2O3 8-20%, SiO2 30-45%, CaO3 1-50%, MgO 2-16%, Fe2O3 0.5-3%, and Mn0 0.5-5%.

[0021] Furthermore, the coating layer thickness is 1 to 5% of the particle size of the main sphere.

[0022] A method for preparing composite tailings porous ceramic balls comprises the following steps:

[0023] (1) Grinding: Wet ball milling is used to obtain the main milling material and the coating material. The fineness of the main milling material is D98 = 2 to 10 μm, and the fineness of the coating material is D98 = 5 to 15 μm;

[0024] (2) Drying: ball-milling the main material and the ball-milling coating material by filter pressing to obtain the main material mud cake and the coating material mud cake, the moisture content of the main material mud cake and the coating material mud cake is 30-35%, and then flash drying is performed to obtain the main material and the coating material, the moisture content of the main material and the coating material is ≤3%;

[0025] (3) Molding: The main material is formed into a main sphere by a rolling method, and then wrapped with a coating material to obtain a green body;

[0026] (4) Firing: The green body is fired in a tunnel kiln to obtain a porous ceramic ball green body;

[0027] (5) Processing: The porous ceramic ball blank is polished, rinsed and dried in sequence to obtain the finished product.

[0028] Furthermore, during the sintering in step (4),

[0029] Low temperature stage: first increase the temperature to 400 degrees at 2 degrees per minute, then increase the temperature to 600 degrees at 0.5 degrees per minute.

[0030] ℃, and then increase the temperature to 900℃ at 5℃ per minute;

[0031] Medium and high temperature stage: oxygenation changes the weak reducing atmosphere into an oxidizing atmosphere, sintering at a slight positive pressure of 5 to 30 Pa, and the temperature rises to 1100°C at 2°C per minute;

[0032] High temperature sintering stage: 1100-1300°C, maintaining a slight positive pressure of 5-30Pa, an oxidizing atmosphere, and a holding time of 2-5h.

[0033] Furthermore, during polishing in step (5), a stirred mill is used for polishing at a linear speed of

[0034] 2~5m / S, polishing time 1~5h.

[0035] The beneficial effects of the present invention are:

[0036] 1. The present invention uses tailings and waste materials in their entirety. Iron ore plays a major role in assisting combustion and generating pores; coal gangue plays a major role in providing heat energy and generating pores; bauxite tailings play a major role in strengthening the matrix; zeolite tailings play an important role in abrasive dirt absorption and sintering uniform pores; blast furnace slag plays a major role in assisting combustion and controlling the amount of pores; through scientific and reasonable proportioning, uniformly porous tailings ceramic balls are prepared, waste minerals are consumed to the greatest extent, and the ceramic sintering temperature is relatively low (the sintering temperature is 1100-1300°C), which is in line with environmental protection and sustainable development.

[0037] 2. The present invention adds zeolite tailings. The crystal structure of zeolite is a three-dimensional grid composed of silicon (aluminum) oxygen tetrahedrons. There are holes and channels of various sizes in the grid, which has great openness and good selective adsorption and ion exchange properties. First, zeolite tailings is a kind of waste solid, and the recycling price is low and environmentally friendly. Secondly, the adsorption and ion exchange properties of zeolite are utilized to greatly reduce the pollutants such as heavy metals and fluorine released into the water during the grinding process of the tailings, thereby reducing secondary pollution. In addition, the unique spatial structure of zeolite can be used as a pore nucleus during the firing process of porous tailings ceramics to ensure the uniformity of the fired bubble pores. At the same time, it can be used as a through-hole structure to avoid uneven bubble pressure during firing, thereby avoiding the generation of uneven large bubble pores.

[0038] 2. The present invention adds coal gangue, which contains a large amount of carbon. The combustion of carbon during the sintering process releases a large amount of heat energy, which has an energy-saving effect. At the same time, the spatial micropores formed by the combustion of carbon are beneficial to the in-situ generation of more uniform and dense foam pores during the sintering process; in addition, the spatial micropores formed by the combustion of carbon are beneficial to the in-situ generation of more uniform and dense foam pores during the sintering process; in addition, the sintering of coal gangue mainly forms mullite and silica, which can be used as ceramic aggregates to enhance the strength of porous ceramics.

[0039] 3. The present invention adds bauxite tailings, which contain a relatively high content of alumina, thereby increasing the strength and wear resistance of the foam ceramic matrix.

[0040] 4. Iron tailings are added in the present invention, and the ingredients contain a large amount of CaO, MgO, and Fe2O3, which are good solvents for ceramic firing. At the same time, iron tailings contain a large amount of volatile substances, which are released during high-temperature firing and are the main material for the formation of pores in this patent.

[0041] 5. Blast furnace slag is used in the present invention. Since a large amount of tailings has been selected in this patent, sufficient volatile gases can be provided during firing to form pores. The blast furnace slag contains a large amount of CaO, MgO, and Fe2O3, which mainly exist in the form of various silicates. It is not easy to produce volatile gases during firing, and it is a good solvent for ceramic firing.

[0042] 6. The present invention uses shell coating technology. A major feature of porous tailings ceramics is that a large amount of glass phase will be formed during firing, which often causes the green bodies to stick to each other. This solution uses inert raw materials (alumina, kaolin, bauxite, etc.) to cover the surface of the glass phase, which can well prevent the porous ceramic balls from sticking to each other during the firing process. There is no need to use a rotary kiln specifically, and the ball blanks are dynamically sintered. At the same time, the coating layer greatly improves the compatibility of the formula itself with the instability of tailings and the tolerance of firing temperature.

[0043] 7. The present invention uses grinding and polishing processing technology. The porous tailings ceramics obtained by firing have a coated outer layer, which is a closed-cell structure, and an inner layer is a porous structure with a large through-porosity and a light specific gravity. The polishing effect of a non-stirred mill is poor. It is preferred to polish with a stirred mill and then rinse to obtain an open porous tailings ceramic ball with a higher roundness. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a cross-sectional structural diagram of the finished product of Example 5;

[0045] Figure 2 This is a cross-sectional structural diagram of the finished product of Example 6;

[0046] Figure 3 This is a cross-sectional structural diagram of the finished product of Example 7; DETAILED DESCRIPTION

[0047] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings.

[0048] Example 1: A composite tailings porous ceramic ball, including a main ball and a coating layer, wherein the main ball includes the following main materials in weight percentage: iron tailings 30%, coal gangue 20%, bauxite tailings 30%, zeolite tailings 10%, blast furnace slag 10%; the iron tailings include the following components in mass percentage: Al2O3 5%, SiO2 70%, CaO 15%, MgO 2%, Fe2O38%. The coal gangue includes the following components in mass percentage: Al2O3 25%, SiO2 50%, CaO

[0049] 2%, Na2O 3.0%, K2O 1.5%, Fe2O3 5%, C 13.5%. Bauxite tailings include the following components by mass percentage: Al2O3 40%, SiO2 40%, CaO 1.5%, Na2O 2.0%, K2O 3.0%, Fe2O3 12%, TiO21.5%. Zeolite tailings include the following components by mass percentage: Al2O3 15%, SiO2 75%, CaO 3%, Na2O 2%,

[0050] K2O 3%, Fe2O3 2%. The blast furnace slag includes the following components in mass percentage: Al2O3 8%, SiO2 45%, CaO 31%, MgO 11%, Fe2O3 2%, Mn0 3%. The coating layer includes a coating material, the coating material is alumina, and the coating layer thickness is 1% of the main sphere particle size.

[0051] Embodiment 2: A composite tailings porous ceramic ball, comprising a main sphere and a coating layer, wherein the main sphere comprises the following main materials in weight percentage: 60% iron tailings, 10% coal gangue, 20% bauxite tailings, 3% zeolite tailings, and 7% blast furnace slag; the iron tailings comprises the following components in mass percentage: 18% Al2O3, 55% SiO2, 2% CaO, 10% MgO, and 15% Fe2O3. The coal gangue comprises the following components in mass percentage: 40% Al2O3, 43.7% SiO2, 0.5% CaO, 0.2% Na2O, 0.1% K2O, 0.5% Fe2O3, and 15% C. Bauxite tailings include the following components in mass percentage: Al2O3 60%, SiO2 20%, CaO 1%, Na2O 1%, K2O 2%, Fe2O3 11%, TiO2 5%.

[0052] The zeolite tailings include the following components in mass percentage: Al2O3 30%, SiO2 60%, CaO4.0%, Na2O1.0%, K2O 2.0%, Fe2O3 3%. The blast furnace slag includes the following components in mass percentage: Al2O3 20%, SiO2 30%, CaO 40%, MgO 2%, Fe2O3 3%, Mn0 5%. The coating layer includes a coating material, the coating material is kaolin, and the coating layer thickness is 2% of the main sphere particle size.

[0053] Embodiment 3: A composite tailings porous ceramic ball, comprising a main sphere and a coating layer, wherein the main sphere comprises the following main materials in weight percentage: 34% iron tailings, 40% coal gangue, 20% bauxite tailings, 1% zeolite tailings, and 5% blast furnace slag; the iron tailings comprise the following components in mass percentage: 15% Al2O3, 45% SiO2, 15% CaO, 10% MgO, and 15% Fe2O3. The coal gangue comprises the following components in mass percentage: 38% Al2O3, 40% SiO2, 1% CaO, 2% Na2O, 1% K2O, 3% Fe2O3, and 15% C. The bauxite tailings include the following components in mass percentage: Al2O3 55%, SiO2 38.15%, CaO 0.3%, Na2O 0.05%, K2O 0.5%, Fe2O3 5%, and TiO2 1%.

[0054] The zeolite tailings include the following components in mass percentage: Al2O3 25%, SiO2 65.5%, CaO 2.0%, Na2O3.0%, K2O 4.0%, Fe2O3 0.5%. The blast furnace slag includes the following components in mass percentage: Al2O3 12%, SiO2 35%, CaO 50%, MgO 2%, Fe2O3 0.5%, Mn0 0.5%.

[0055] The coating layer includes a coating material, the coating material is bauxite, and the thickness of the coating layer is 3% of the particle size of the main sphere. Example 4: A composite tailings porous ceramic ball includes a main sphere and a coating layer, wherein the main sphere includes the following main materials in weight percentage: iron tailings 34%, coal gangue 10%, bauxite tailings 50%, zeolite tailings 1%, and blast furnace slag 5%; the iron tailings include the following components in mass percentage: Al2O3 11%, SiO2 65%, CaO 7%, MgO 6%, and Fe2O3 11%. The coal gangue includes the following components in mass percentage: Al2O3 40%, SiO2 50%, CaO1%, Na2O 1.2%, K2O 0.8%, Fe2O3 2%, and C 5%. The bauxite tailings include the following components in mass percentage: Al2O3 50%, SiO2 30%, CaO 1.5%, Na2O2.0%, K2O3.0%, Fe2O3 8.5%, and TiO2 5%.

[0056] Zeolite tailings include the following components in mass percentage: Al2O3 20%, SiO2 68%, CaO2.0%, Na2O3.0%, K2O 2%, Fe2O3 3%. Blast furnace slag includes the following components in mass percentage: Al2O3 14%, SiO2 35%, CaO31.5%, MgO 16%, Fe2O3 3%, Mn0 0.5%.

[0057] The coating layer comprises a coating material, which is one or more of alumina, kaolin and bauxite, and the thickness of the coating layer is 5% of the particle size of the main sphere.

[0058] Embodiment 5: A method for preparing a composite tailings porous ceramic ball, comprising the following steps: Grinding: using wet ball milling to obtain a ball milling main material and a ball milling coating material, wherein the ball milling main material has a fineness D98 of 2 to 10 μm, and the ball milling coating material has a fineness D98 of 5 to 15 μm;

[0059] Drying: ball-milling the main material and the ball-milling coating material by filter pressing to obtain the main material mud cake and the coating material mud cake, the moisture content of the main material mud cake and the coating material mud cake is 30%, and then flash drying is performed to obtain the main material and the coating material of the formula of Example 1, the moisture content of the main material and the coating material is 3%;

[0060] Molding: The main material is formed into a main sphere by a rolling method, and then wrapped with a coating material to obtain a green body;

[0061] Firing: The green body is fired in a tunnel kiln to obtain a porous ceramic ball green body.

[0062] Low temperature stage: first increase the temperature to 400 degrees at 2 degrees per minute, then increase the temperature to 600 degrees at 0.5 degrees per minute, and then increase the temperature to 900 degrees at 5 degrees per minute;

[0063] Medium and high temperature stage: oxygen is added to convert the weak reducing atmosphere into an oxidizing atmosphere, sintering is carried out at a slight positive pressure of 5Pa, and the temperature is increased by 2℃ per minute to 1100℃;

[0064] Insulation sintering stage: at 1100℃, maintain a slight positive pressure of 5-30Pa, an oxidizing atmosphere, and continue to keep warm for 2-5h.

[0065] Processing: The porous ceramic ball blank is polished, rinsed and dried in sequence to obtain the finished product; during polishing, a stirring mill is used for polishing, the linear speed is 2m / S, and the polishing time is 1h.

[0066] Embodiment 6: A method for preparing composite tailings porous ceramic balls, comprising the following steps:

[0067] Grinding: Wet ball milling is used to obtain the main milling material and the coating material. The fineness of the main milling material is D98 = 2 to 10 μm, and the fineness of the coating material is D98 = 5 to 15 μm;

[0068] Drying: ball-milling the main material and the ball-milling coating material by filter pressing to obtain the main material mud cake and the coating material mud cake, the moisture content of the main material mud cake and the coating material mud cake is 32%, and then flash drying is performed to obtain the main material and the coating material of the formula of Example 2, the moisture content of the main material and the coating material is 2%;

[0069] Molding: The main material is formed into a main sphere by a rolling method, and then wrapped with a coating material to obtain a green body;

[0070] Firing: The green body is fired in a tunnel kiln to obtain a porous ceramic ball green body.

[0071] Low temperature stage: first increase the temperature to 400 degrees at 2 degrees per minute, then increase the temperature to 600 degrees at 0.5 degrees per minute, and then increase the temperature to 900 degrees at 5 degrees per minute;

[0072] Medium and high temperature stage: oxygen is added to convert the weak reducing atmosphere into an oxidizing atmosphere, sintering is carried out at a slight positive pressure of 15Pa, and the temperature is increased by 2℃ per minute to 1100℃;

[0073] Insulation sintering stage: heat to 1200°C, maintain a slight positive pressure of 5 to 30 Pa, an oxidizing atmosphere, and then continue to keep warm at this temperature for 2 to 5 hours.

[0074] Processing: The porous ceramic ball blanks are polished, rinsed and dried in sequence to obtain the finished product; during polishing, a stirring mill is used for polishing, the linear speed is 3m / S, and the polishing time is 3h.

[0075] Embodiment 7: A method for preparing composite tailings porous ceramic balls, comprising the following steps:

[0076] Grinding: Wet ball milling is used to obtain the main milling material and the coating material. The fineness of the main milling material is D98 = 2 to 10 μm, and the fineness of the coating material is D98 = 5 to 15 μm;

[0077] Drying: ball-milling the main material and the ball-milling coating material by filter pressing to obtain the main material mud cake and the coating material mud cake, the moisture content of the main material mud cake and the coating material mud cake is 35%, and then flash drying is performed to obtain the main material and the coating material of the formula of Example 3, the moisture content of the main material and the coating material is 1%;

[0078] Molding: The main material is formed into a main sphere by a rolling method, and then wrapped with a coating material to obtain a green body;

[0079] Firing: The green body is fired in a tunnel kiln to obtain a porous ceramic ball green body.

[0080] Low temperature stage: first increase the temperature to 400 degrees at 2 degrees per minute, then increase the temperature to 600 degrees at 0.5 degrees per minute, and then increase the temperature to 900 degrees at 5 degrees per minute;

[0081] Medium and high temperature stage: oxygen is added to convert the weak reducing atmosphere into an oxidizing atmosphere, sintering is carried out at a slight positive pressure of 30Pa, and the temperature is increased by 2℃ per minute to 1100℃;

[0082] Insulation sintering stage: heat to 1300°C, maintain a slight positive pressure of 5 to 30 Pa, an oxidizing atmosphere, and then continue to keep warm at this temperature for 2 to 5 hours.

[0083] Processing: The porous ceramic ball blank is polished, rinsed and dried in sequence to obtain the finished product; during polishing, a stirring mill is used for polishing, the linear speed is 5m / S, and the polishing time is 5h.

[0084] Test: A handheld USB digital microscope was used to observe the pore distribution of the ball blank cross section, with a magnification of 500 times; the volume density and porosity of the sphere were tested using the "GB / T 1966-1996 Test Method for Porous Ceramics Porosity and Bulk Density", and the test results are as follows:

[0085] Example <![CDATA[Bulk density g / cm 3 > Porosity Example 5 1.187 58.2% Example 6 1.001 63.2% Example 7 1.575 42.1%

[0086] The described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A composite tailings porous ceramic ball, comprising a main sphere and a coating layer, characterized in that: The main sphere comprises the following main materials in weight percentage: 30-60% iron tailings, 10-40% coal gangue, 20-50% bauxite tailings, 1-10% zeolite tailings, and 5-10% blast furnace slag; the coating layer comprises a coating material, which is one or more of alumina, kaolin, and bauxite.

2. The composite tailings porous ceramic ball according to claim 1, characterized in that: The iron tailings include the following components in mass percentage: Al2O3 5-18%, SiO2 45-70%, CaO 2-15%, MgO 2-10%, and Fe2O3 8-15%.

3. The composite tailings porous ceramic ball according to claim 1, characterized in that: The coal gangue comprises the following components in percentage by mass: Al2O3 25-40%, SiO2 40-50%, CaO 0.5~2%, Na2O 0.2~3.0%, K2O 0.1~1.5%, Fe2O3 0.5~5%, C 5~15%.

4. The composite tailings porous ceramic ball according to claim 1, characterized in that: The bauxite tailings include the following components in mass percentage: Al2O3 40-60%, SiO2 20-40%, CaO 0.3-1.5%, Na2O 0.05-2.0%, K2O 0.5-3.0%, Fe2O3 5-12%, and TiO2 1-5%.

5. The composite tailings porous ceramic ball according to claim 1, characterized in that: The zeolite tailings include the following components in mass percentage: Al2O3 15-30%, SiO2 60-75%, CaO2.0-4.0%, Na2O 1.0-3.0%, K2O2.0-4.0%, and Fe2O3 0.5-3%.

6. The composite tailings porous ceramic ball according to claim 1, characterized in that: The blast furnace slag comprises the following components in mass percentage: Al2O3 8-20%, SiO2 30-45%, CaO31-50%, MgO 2-16%, Fe2O3 0.5-3%, and Mn0 0.5-5%.

7. The composite tailings porous ceramic ball according to claim 1, characterized in that: The coating layer thickness is 1-5% of the main spherical particle size.

8. A method for preparing composite tailings porous ceramic balls according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Grinding: Wet ball milling is used to obtain the main milling material and the coating material. The fineness of the main milling material is D98 = 2 to 10 μm, and the fineness of the coating material is D98 = 5 to 15 μm; (2) Drying: ball-milling the main material and the ball-milling coating material by filter pressing to obtain the main material mud cake and the coating material mud cake, the moisture content of the main material mud cake and the coating material mud cake is 30-35%, and then flash drying is performed to obtain the main material and the coating material, the moisture content of the main material and the coating material is ≤3%; (3) Molding: The main material is formed into a main sphere by a rolling method, and then wrapped with a coating material to obtain a green body; (4) Firing: The green body is fired in a tunnel kiln to obtain a porous ceramic ball green body; (5) Processing: The porous ceramic ball blank is polished, rinsed and dried in sequence to obtain the finished product.

9. The method for preparing composite tailings porous ceramic balls according to claim 8, characterized in that: During the firing in step (4), Low temperature stage: first increase the temperature to 400 degrees at 2 degrees per minute, then increase the temperature to 600 degrees at 0.5 degrees per minute, and then increase the temperature to 900 degrees at 5 degrees per minute; Medium and high temperature stage: oxygen is added to convert the weak reducing atmosphere into an oxidizing atmosphere, sintering is carried out at a slight positive pressure of 5 to 30 Pa, and the temperature is increased by 2°C per minute to 1100°C; Insulation sintering stage: heating to 1100-1300℃, maintaining a slight positive pressure of 5-30Pa, oxidizing atmosphere, Then continue to keep warm at this temperature for 2 to 5 hours.

10. The method for preparing composite tailings porous ceramic balls according to claim 8, characterized in that: During the polishing in step (5), a stirred mill is used for polishing, the linear speed is 2 to 5 m / s, and the polishing time is 1 to 5 hours.

Citation Information

Patent Citations

  • Novel sound absorbing material for buildings and preparation method thereof

    CN108395211A

  • Preparation method of low-temperature porous ceramic material

    CN115231943A

  • Low-shrinkage mullite-based porous ceramic and preparation method thereof

    CN115231944A

  • Industrial waste slag haycite and preparation method thereof

    CN103159483A

  • Method for producing multifunctional quincuncial light ceramsite with bauxite tailings and through holes

    CN106631137A